TINJAUAN NARATIF EFEKTIVITAS DAN KEAMANAN ANTIRETROVIRAL PADA PASIEN DENGAN KOINFEKSI HIV-HBV - Rizky Yuliatus Solicha; Vitarani Dwi Ananda Ningrum (Jurnal Insan Farmasi Indonesia, 2026)
HIV-HBV coinfection remains a major global health challenge associated with increased morbidity and mortality. Various studies have evaluated the effectiveness and safety of antiviral therapies in coinfected patients; however, the findings remain inconsistent. This narrative review aimed to summarize the current evidence regarding the effectiveness and safety of antiretroviral therapy in patients with HIV-HBV coinfection. Literature searches were conducted through PubMed and Google Scholar for studies published between 2014 and 2025 using keywords related to HIV, hepatitis B, nucleos(t)ide analogues, interferon alfa, effectiveness, and safety. The findings demonstrated that the TLD regimen (tenofovir, lamivudine, and dolutegravir) showed superior virological outcomes compared with TLE (tenofovir, lamivudine, and efavirenz), including higher viral suppression rates and greater CD4 cell recovery. Nucleos(t)ide analogues such as entecavir and telbivudine effectively reduced HBV DNA levels and improved liver function markers. However, several adverse drug reactions were reported, including dizziness, nausea, vomiting, metabolic disturbances, and renal impairment, particularly with tenofovir-containing regimens. Interferon alfa also demonstrated potential benefits in enhancing seroconversion. Overall, TLD is considered the preferred regimen due to its superior efficacy and resistance profile, although careful monitoring for adverse effects remains essential.